Factors Hindering Quality Performance in Construction Projects: An Empirical Study - Raw’a Hijazi (Journal of Management Research, 2024)
Construction industry is crucial for the economy of any country. Learning from failure is important to reach effective quality performance in construction projects. This will, in turn, contribute to the development of the construction industry and the country as a whole. Although quality is an important criterion in the project management success, but it receives less attention than cost and time in project management literature. Moreover, critical success factors (CSFs) are identified more often than critical failure factors (CFFs) in construction literature. Hence, there is still a lack of attention on critical failure factors affecting quality performance in construction projects. Construction industry is full of uncertainties, especially in the current era of COVID-19 Pandemic. This adds to the necessity of studying critical failure factors in construction industry. This study aims to identify the critical factors that have adverse effect on quality performance in construction projects, address their relative importance, and suggest ways to attain good quality performance in construction projects. Based on literature review, an initial list of failure attributes of quality performance in construction projects was prepared. Then it was refined based on suggestions from experienced professionals in the construction industry in the Jordanian context. A questionnaire was distributed to experts in the construction industry. The responses were analyzed using Statistical Package for the Social Sciences (SPSS). The analyses used here are factor analysis and tests of its appropriateness. Using these analyses, the most critical factors that impede quality performance in construction were identified and ranked. The study revealed that the most influencing failure factors are the managerial factor, the culture and environment factor, and the contractor factor.